Differences on growth and grain yield between four pearl millet cultivars - Geraldo, José; Rossiello, Roberto Oscar Pereyra; Araújo, Adelson Paulo; Pimentel, Carlos (Pesquisa Agropecuaria Brasileira, 2000)
The growth patterns of four cultivars of pearl millet (Pennisetum glaucum (L.) R. Brown), and their relationships with grain yield were evaluated through plant growth analysis. In a field experiment in Haplaquult soil, the biomass of cultivars BN-2 and IAPAR (Brazilian cultivars for forage production), Guerguera and HKP (African cultivars for grain yield) was sampled 11 times. Brazilian cultivars presented earlier flowering and higher shoot dry matter in the beginning of the growth cycle, but African cultivars were superior after flowering. There was no significant difference among cultivars for N concentration of tissues and grains. Brazilian cultivars produced double number of panicles, and a more intense tillering. African cultivars presented higher grain yield than Brazilian cultivars (403 versus 268 g m-2), due to 1,000-grain weight, and panicle length almost twice greater. The inferior productivity of forage cultivars was in part due to the low planting density used.
Keywords: Pennisetum glaucum; genotypes; leaf area; biomass; panicles; feed grasses; growth rate; yields